ANALISA MASALAH-MASALAH YANG MUNCUL DALAM PEMEKARAN WILAYAH BARU PADA PENYELENGARAAN OTONOMI DAERAH - Surya Akbar (JIAGANIS, 2019)
Abstract :This study aims to understand the implementation of regional autonomy or decentralization which aims to improve service quality, regional competitiveness and community welfare, but in this study it will further explain clearly that regional autonomy is able to provide stimulus to the regions to become new autonomous regions or new areas of expansion. The formation of a new autonomous region is normal if it is able to realize the desires of the local people because what is clear with the emergence of new autonomous regions will also raise new problems. There are positive impacts and negative impacts overshadowing the implementation of regional autonomy especially for the new autonomous region The birth of the new autonomous region is expected to be based on the wishes of the people who are able to increase community participation in building the region and not at the wishes of the local elite.Keywoord : Regional autonomy, decentralization, participation and local elite